Functional characterization of potential drug targets in Schistosoma mansoni and evaluation of disulfiram and Schl-32.028 as promising anti-schistosomal compounds - Beutler, Mandy; Justus Liebig University Giessen (My University, 2022)
As a neglected tropical disease (NTD), schistosomiasis has a tremendous impact on humans and animals worldwide. Praziquantel (PZQ), an effective drug to kill adult schistosomes, has been used since the 1970s, and there is evidence of emerging resistance. There are several ways to expand the range of drugs against this disease. One is ”drug repurposing”, which is the use of existing drugs for other applications than those originally approved. Studies on the Abl kinase inhibitor imatinib (Glivec, STI571) showed tremendous effects on adult S. mansoni in vitro, which could not be confirmed in a mouse infection model because of the binding capacities of α-1 acid glycoprotein (AGP) and serum albumin protein to imatinib. However, in the research group of Prof. C. G. Grevelding, an aldehyde dehydrogenase (Aldh) was found in the tegument of males. Since the tegument is a naturally occurring surface of the parasite for the host immune system, it seems worthwhile to target its components. As first in vitro studies revealed an influence of the Aldh inhibitor disulfiram (DSF) on adult worms, its impact was investigated in detail. Doses ≥ 25 μM showed effects on pairing stability, attachment ability, motility, and oviposition but also on the tegument structure and the gonads of both genders. Furthermore, stem cell proliferation was negatively affected. The effects of DSF alone were enhanced by concomitant treatment with copper, comparable to the DSF metabolite copper bis(diethyldithiocarbamate). Co-administration of DSF, copper, and copper chelators resulted in a dose-dependent reversal of the toxic effects of DSF/Cu with bathocuproinedisulfonic acid (BCPD) but not with ethylenediamine tetraacetic acid(EDTA). These results suggest that DSF has high anti-schistosomal potential, which might be copper-dependent. The synthesized DSF derivative Schl-32.028, provided by a cooperation partner (working group of Prof. M. Schlitzer, Philipps-University Marburg) was also analyzed for its anti-schistosomal potential. Schl-32.028 impaired worm viability, altered stem cell proliferation, and induced oxidative stress-related genes in females. Another part of this work comprised the cloning and expression of two Aldhs (SmAldh1 and SmAldh2), two Abelson-like (Abl) kinases (SmAbl1 and SmAbl2), and the Src/Abl hybrid kinase SmTK6 for enzyme characterization. To this end, the respectivesequences were cloned into expression vectors and tested for expression in different E. coli strains In contrast to E. coli pLysS, both SmAldhs and SmTK6 were successfully expressed as full-length proteins in E. coli LOBSTR-RIL, whereas no full-length protein of either SmAbl was detected. Instead, the tyrosine kinase (TK) domains (TKDs) of SmAbl1 and SmAbl2 were successfully expressed in E. coli LOBSTR-RIL. Since strong protein signals were detected in the pellet fractions, protein solubility enhancement analysis was performed. To this end, both SmAldhs and SmTK6 were cloned for expression asfusion proteins with maltose-binding protein (MBP) and expressed in E. coli LOBSTR-RIL. Solubility of MBP:SmAldh1 and MBP:SmTK6 seemed to increase slightly upon fusion, while this was not the case for MBP:SmAldh2. Finally, it was tested whether full-length proteins or truncated versions (TKDs) of SmAbl kinases can be expressed in HEK293-6E (EBNA1) cells, which failed. Since SmAldh1 was expressed in sufficient quantities, enzyme activity tests were established together with the working group of Prof. P. Czermak (University of Applied Sciences Mittelhessen, Giessen). Enzyme assays demonstrated enzyme activity, which was increased after addition of calcium (Ca2+) or magnesium (Mg2+). Functional analyses of Smaldh1 and Smaldh2 were performed parallel to the enzyme characterization. Both Smaldh transcripts were transcribed in adult worms as determined by quantitative real-time polymerase chain reaction (qRT-PCR) analyses, and whole mount in situ hybridization (WISH) revealed a broad transcript distribution in both genders. During ribonucleic acid (RNA) interference (RNAi) observation periods between 14 - 21 days (d), physiological, morphological and cell-biological parameters were monitored such as pairing stability and egg production, morphological changes of tissues including the gonads, stem cell proliferation, and the transcription of selected genes potentially involved in oxidative stress response, cell cycle, apoptosis, as well as stem cell activity, respectively. The knock down of Smaldh1 and Smaldh2 showed no clear effects of the observed parameters except Smaldh2, which caused an ovary phenotype. Double-knock down of both Smaldhs also had no clear effect. Since Aldhs are involved in oxidative stress response, their possible involvement in the reaction towards the stressor H2O2 was investigated. For this, S. mansoni couples were treated with either Smaldh1 or Smaldh2 double-stranded RNA (dsRNA) and exposed to H2O2 for an additional 3 d period. The attachment capacity was slightly lowered in the RNAi treatment groups of Smaldh1, while it was increased after Smaldh2 knock down. While the stress-related gene transcript levels of Smgpx and Smsod were downregulated in females after both treatment combinations, both genes and additionally Smsodex were upregulated in males only after Smaldh1 knock down. These data suggested a possible role of SmAldhs in stress-response pathways, but this needs further validation. Further RNAi experiments against Smabl1 appeared to impede differentiation of immature oocytes, as their number increased, while the number of mature oocytes decreased. Knock down of Smabl2 induced the formation of cell-free spaces in the ovaries of females and in the testes of males. A double knock down of Smabl1 and Smabl2 combined the observed phenotypes in the gonads. When Smtk6 was knocked down, the number of immature oocytes increased and mature oocytes appeared partly granulated, whereas male testes showed cell-free spaces. Upregulation of Smtk6 was observed after knock down of both Smabls, while in turn the transcripts of both Smabls were upregulated after knock down of Smtk6. This suggests that these kinases could have redundant functions.
Keywords: Aldehyde dehydrogenase; Disulfiram; Drug repurposing; Drug target characterization; Abl kinases; ddc:000; ddc:500; ddc:570